OutFin, a multi-device and multi-modal dataset for outdoor localization based on the fingerprinting approach - Fahad Alhomayani (Nature Portfolio, 2021)
Measurement(s) outdoor location fingerprints • WiFi data • Bluetooth data • cellular signal strengths • Coordinate Technology Type(s) smartphone • magnetometer • Accelerometer • gyroscope • barometer • ambient light sensor Sample Characteristic - Location global Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.13370291